Catástrofes Naturais. Uma abordagem global - Luciano Lourenço (Riscos e Catástrofes, 2020)
This publication, entitled "Natural Disasters. A Global Approach" brings together a set of texts devoted specifically to disasters that have as their origin phenomena of nature, full manifestation of the so-called natural hazards. Throughout each of these chapters, we have sought to clarify the conceptual and methodological aspects inherent in each of the risks under analysis, their systematization or typification, effects and consequences, particularly for the Human Being, and examples of their manifestation. Although with distinct characteristics and influenced by different factors, the extent of natural disasters is evident, affecting the generality of human societies and conditioning their activity in almost all parts of the earth´s surface. It is our hope that this work will fulfill its intended purpose and become a valuable working tool and a vehicle for disseminating information and raising awareness of natural disasters.